P205 21 years of SHIELD: decreasing incidence of Occupational Asthma in the West Midlands, UK?. (14th November 2013) - Walters, GI; Kirkham, A; McGrath, EE; Moore, VC; Robertson, AS; Burge, PS
Abstract : Introduction: Notifications of occupational asthma (OA) to the West Midlands SHIELD reporting scheme have declined between 1991 and 2011. This may be due in part to reporter fatigue or restrictions on reporting, under-recognition, or true reduction in incidence of OA due to workplace control measures. We aimed to describe trends in reports of OA to the SHIELD database over a 21-year period and investigate reasons for any changes. Methods: Descriptive statistics were performed on demographic and annual notification count data (for total notifications and individual causative agents). Count data were scaled to give a count per million workers using West Midlands' mid-year population estimates. A number of statistical analyses were undertaken to calculate trends in annual notifications: (i) non-parametric Kendall tau-b correlation (reference method), (ii) a negative binomial regression model, calculating incident rate ratios (IRRs), including a step-change analysis, and (iii) a logistic regression model calculating annual reporting odds ratios for 13 common causative agents. Results: 1637 cases of OA were notified between 1991 and 2011. Most cases were notified from the Birmingham Heartlands specialist clinic and notifications made elsewhere in the West Midlands fell from 16 per million workers in 1995 to zero in 2004, with very few cases (4 per million workers) after that. A significant non-linear decrease in annual total notifications was observed over the study period (IRR = 1.056; 95% CI = 1.012–1.102; p = 0.012), as was the case for most causative agents studied. However cleaning products showed a 6% increase in notifications year-on-year (IRR = 1.056; 95% CI = 1.012–1.102; p = 0.012; Figure 1 ). Although the incidence of isocyanate-related OA decreased significantly after 2005, the proportion of annual notifications due to isocyanates relative to other agents increased year on year (tau = 0.43; p = 0.007). Conclusions: Falling incidence of OA between 1991 and 2011 is explained in part by under-recognition by healthcare professionals, and by reporter fatigue, though for some causative agents this may be attributed in part to better workplace controls. Isocyanates remain the most common cause of OA but reports have fallen recently along with colophony, latex and glutaraldehyde, which have almost disappeared. Conversely cleaning product related OA is increasingly recognised.